Reading Anomaly of Tourist Satisfaction in Pilgrimage Tourist Destination of Sunan Muria Tomb, Kudus, Central Java - Prihantoro, Fahmi; Makhasi, Ghifari Yuristiadhi Masyhari; Abdillah, Muhammad Rosyid (E-Journal of Tourism; Volume 6 Number 1 (March 2019)DO - 10.24922/eot.v6i1.42917, 2019)
Satisfaction of tourists is the key success for tourism destination sustainability because it is a reason for tourists to return to the destination. This research wanted to see the anomaly at Sunan Muria Tomb, Kudus, Central Java related to the satisfaction of tourists on the limited accessibility which is one of the four components that must be owned by a tourist destination according to Cooper, et.al. (1993), in addition to attractions, amenitas, and ancillary service. This research uses descriptive qualitative method and phenomenological approach. Methods of data collection with field observation, in-depth interviews and literature study. The results of this study indicate that access to the tomb of Sunan Muria, both with the stairs and motorcycle taxi is still far from feasible. The stairs are not flat because it is made of stone times, quite steep and there is no cover on so if the rain down the stairs become muddy and slippery. Although there is motorcycle taxi service, but the level of security (riding safety) is also low. This destination for tourists still has interesting attractions as pilgrimage destination with adequate amenitas (food stalls and lodgings) and ancelery service (from the YM2SM or Sunan Muria foundation and the Tourism Office of Kudus District Government), although accessibility is very problematic. All the visitors complained about this, but that did not dampen interest for a return visit. This is an anomaly in the Sunan Muria pilgrimage destination.